Cocaine and benzoylecgonine oral fluid on‐site screening and confirmation. Issue 3 (9th March 2016) - Ellefsen, Kayla N.; Concheiro, Marta; Pirard, Sandrine; Gorelick, David A.; Huestis, Marilyn A.
Abstract : Accurate on‐site devices to screen for drug intake are critical for establishing whether an individual is driving under the influence of drugs (DUID); however, on‐site oral fluid (OF) cocaine device performance is variable. We evaluated the performance of a newly developed benzoylecgonine (BE) test‐strip for the Draeger® DrugTest 5000 device (20 µg/L cut‐off) with equivalent cross reactivity for cocaine and BE. Ten cocaine users provided OF, collected with the Draeger cassette and Oral‐Eze® and StatSure Saliva Sampler TM devices, up to 69 h following 25 mg intravenous cocaine administration. All screening results were confirmed by a validated two‐dimensional‐gas chromatography‐mass spectrometry (2D‐GC‐MS) method for cocaine and/or BE. Cocaine test‐strip median T last for screening only results was 6.5 h, and 6.5 h with Oral‐Eze® and 4 h for StatSure OF confirmation for cocaine and/or BE at 1, 8, and 10 µg/L; sensitivity, specificity, and efficiency ranged from 85.5 to 100% and 83.3 to 100% for cocaine only confirmation at 8 and 10 µg/L. For the BE test‐strip, median T last was 12.5 h for screening only and confirmation for cocaine and/or BE at all three cut‐offs; sensitivity, specificity, and efficiency ranged from 85.5 to 97.5% and 78.4 to 97.4% with cocaine and/or BE confirmation at 8 and 10 µg/L cut‐offs, respectively. The Draeger cocaine test‐strip with cocaine only confirmation offers a useful option for monitoring the acute intoxication phase of DUID; additionally the BE test‐strip with cocaine and/or BE confirmation increases the length of detection of cocaine intake for workplace drug testing, drug court, parole, pain management, drug treatment programs and both the acute cocaine intoxication and cocaine crash/fatigue phase of DUID. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We evaluated for the first time oral fluid (OF) performance characteristics of the new Draeger DrugTest 5000 benzoylecgonine (BE) test‐strip compared with the original cocaine test‐strip at different confirmation cutoffs following controlled cocaine administration. The cocaine test‐strip with cocaine only OF confirmation is a suitable option for monitoring driving under the influence of drugs, whereas the BE test‐strip with a cocaine and/or BE confirmation is better suited for workplace drug testing, drug court, parole, pain management, and drug treatment monitoring.